The Effect of Dimethyl Sulfoxide on Supercoiled DNA Relaxation Catalyzed by Type I Topoisomerases - Lv, Bei (2015)
The effects of dimethyl sulfoxide (DMSO) on supercoiled plasmid DNA relaxation catalyzed by two typical type I topoisomerases were investigated in our studies. It is shown that DMSO in a low concentration (less than 20%, v/v) can induce a dose-related enhancement of the relaxation efficiency of Escherichia coli topoisomerase I (type IA). Conversely, obvious inhibitory effect on the activity of calf thymus topoisomerase I (type IB) was observed when the same concentration of DMSO is used. In addition, our studies demonstrate that 20% DMSO has an ability to reduce the inhibitory effect on EcTopo I, which was induced by double-stranded oligodeoxyribonucleotides while the same effect cannot be found in the case of CtTopo I. Moreover, our AFM examinations suggested that DMSO can change the conformation of negatively supercoiled plasmid by creating some locally loose regions in DNA molecules. Combining all the lines of evidence, we proposed that DMSO enhanced EcTopo I relaxation activity by (1) increasing the single-stranded DNA regions for the activities of EcTopo I in the early and middle stages of the reaction and (2) preventing the formation of double-stranded DNA-enzyme complex in the later stage, which can elevate the effective concentration of the topoisomerase in the reaction solution.